Analyze The Activities Of Oral Motor Exercise Intervention In Stroke Patients In Neurology Ward: Case Report: Analisis Asuhan Keperawatan Penerapan Intervensi Keperawatan Oral Motor Exercise Pada Pasien Stroke Iskemik Di Ruang Neurologi: Laporan Kasus - Dian Aryanti; Masfuri (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
The incidence of dysphagia was found to occur in stroke patients 19% to 81%.. Nurses are one of the health profesionalhas an important role to management dysphagia. Delay management treatments of dysphagia lead complications suchas pneumonia, malnutrition, dehydration, even death. The purpose of this paper to analyze the activities of oral motorexercise intervention in stroke patients in restoring swallowing function. Oral motor exercise is an exercise in themovement of the tongue, lips, and jaw used for swallowing exercises. Mr. R is 62 years old had ischemic stroke who hascentral NVII sinistra paresis and NXII sinistra paresis so that it is disturbed in the swallowing process. Oral motorexercise is conducted once a day in 10 minutes for 6 days. Screening used Massey Bedside Swallowing Screen (MBSS)and evaluation of intervention using royal Adelaide Prognostic Index for Dysphagic Stroke (RAPIDS). The results showedan improvement in swallowing function assessed by the RAPIDS Test (Royal Adelaide Prognostic Index for DysphagicStroke). The RAPIDS score before the intervention was 78, and the RAPIDS score after the intervention was 91. Basedon this research occur a significant change in the improvement of swallowing function in stroke patients. This paperexpected to be information in the field of nursing in the application of nursing care to stroke patients with dysphagia withthe provision of oral motor exercise.